The attention-deficit/hyperactivity disorder model for traumatic dental injuries: a critical review and update of the last 10 years - SABUNCUOĞLU, OSMAN TALAT (WILEY, 2017)
It has been more than 10 years since the proposal of attention-deficit/hyperactivity disorder (ADHD) model as an explanatory construct for traumatic dental injuries (TDIs) in children. The aim of this review was to address developments in the study of the issue after 2005-2016. A systematic literature search covering the period from 2005 to 2016 was conducted on PubMed, the Cochrane library and Google Scholar using relevant keywords. Fourteen studies exploring the relationship between ADHD and TDIs from 2005 and onward (including the proposal paper) were identified. Of the 12 controlled studies, nine reported confirming findings for a link with ADHD in the occurrence of TDIs. More than one-third of all children with ADHD may suffer from TDIs. In ADHD children, the most common types of injury were uncomplicated/complicated crown fractures and subluxation of maxillary central incisors resulting from falls and collisions. There is also evidence that ADHD represents an independent risk factor other than the well-established risk factor of incisor overjet. Over the last 10 years, convincing evidence has accumulated that ADHD is an important and common risk factor for TDIs. Increased awareness and side-by-side work of medical, dental and mental professionals at both clinical and research settings are necessary.
Keywords: dental trauma; traumatic dental injury; attention-deficit; hyperactivity disorder; OF-THE-LITERATURE; RISK-FACTORS; CHILDREN; BEHAVIOR; EPIDEMIOLOGY; ADOLESCENTS; SYMPTOMS; ADHD